2020
DOI: 10.3390/ma13132966
|View full text |Cite
|
Sign up to set email alerts
|

The Acoustic Emission Method Implementation Proposition to Confirm the Presence and Assessment of Reinforcement Quality and Strength of Fiber–Cement Composites

Abstract: This article proposes to use the acoustic emission (AE) method to evaluate the degree of change in the mechanical parameters of fiber–cement boards. The research was undertaken after a literature review, due to the lack of a methodology that would allow nondestructive assessment of the strength of cement–fiber elements. The tests covered the components cut out from a popular type of board available on the construction market. The samples were subjected to environmental (soaking in water, cyclic freezin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The article by [ 34 ] proposes using the acoustic emission (AE) method to evaluate the degree of change in the mechanical parameters of fiber cement boards. The research was undertaken after a literature review, due to the lack of a methodology that would allow nondestructive assessment of the strength of cement–fiber elements.…”
Section: Description Of the Articles Presented In The Issuementioning
confidence: 99%
See 1 more Smart Citation
“…The article by [ 34 ] proposes using the acoustic emission (AE) method to evaluate the degree of change in the mechanical parameters of fiber cement boards. The research was undertaken after a literature review, due to the lack of a methodology that would allow nondestructive assessment of the strength of cement–fiber elements.…”
Section: Description Of the Articles Presented In The Issuementioning
confidence: 99%
“…According to the authors, the methodology used allows the control of cement–fiber boards in use. The registration and analysis of active processes under the effect of payloads makes it possible to distinguish mechanisms occurring inside the structure of the elements, and to formulate a quick response to the situation when the signals indicate a decrease in the strength of the boards [ 34 ].…”
Section: Description Of the Articles Presented In The Issuementioning
confidence: 99%
“…Their purpose is also to determine the condition of the material’s interior. For this purpose, the following methods are used: X-ray, scanning microscopy, DTA and TGA tests, thermoluminescence, colorimetry, and chemical or petrographic analysis, as well as evaluation methods based on porosity measurements using mercury porosimetry or by assessing the density of micro-scratches [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is effective for detecting and identifying increasing material defects. Thanks to its sensitivity, it can detect processes such as the formation and development of microcracks, the movement of dislocation groups, cracking, sliding, and separation of sediments [ 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, based on the performed research, the authors have observed that the frequency of events is one of the most variable parameters of acoustic emission, sensitive to changes in the mechanical parameters of a material. Therefore, they performed an analysis that allowed them to determine the significance of these changes and to associate them with a specific degree of reduction of the strength of cellulose–cement elements [ 41 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%